Upconversion luminescence of Er3 +/Yb3 + and their role in the stabilization of cubic NaLaF4 nanocrystals in transparent oxyfluoride glass ceramics - Krieke, Guna; Sarakovskis, Anatolijs; Springis, Maris (Elsevier B.V., 2018)
Novel Er3 + and Yb3 + doped transparent oxyfluoride glass ceramics containing NaLaF4 nanocrystals were prepared from oxyfluoride glasses with general composition of Na2O-NaF-LaF3-Al2O3-SiO2. The crystallization processes, changes in morphology and upconversion luminescence were analyzed. The heat treatment of the precursor glasses promoted the formation of hexagonal NaLaF4 and an unidentified fluorite type compound. An enhancement of upconversion luminescence with the introduction of YbF3 in the glass ceramics was detected and indicated an efficient energy transfer from Yb3 + to Er3 +. The local environment of Er3 + in hexagonal NaLaF4 and the fluorite phase was analyzed using site-selective spectroscopy and compared with polycrystalline ceramics. The incorporation of Er3 + ions in three non-equivalent cationic sites in the crystalline lattice of hexagonal NaLaF4 nanocrystals was observed. The local environment of erbium ions in the fluorite phase was found to be similar to α-NaYF4 suggesting the formation of Er3 + and Yb3 + stabilized α-NaLaF4. ----- / / / ---- This is the pre-print version of the following article: G. Krieke, A. Sarakovskis, M. Springis, Upconversion luminescence of Er3 +/Yb3 + and their role in the stabilization of cubic NaLaF4 nanocrystals in transparent oxyfluoride glass ceramics, Journal of Non-Crystalline Solids (2018), which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S0022309317306075?via%3Dihub. This article may be used for non-commercial purposes in accordance with Elsevier Terms and Conditions for Sharing and Self-Archiving. CC BY-NC-ND
CC BY-NC-ND
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Upconversion; Site-selective spectroscopy; NaLaF4; Oxyfluoride; Glass ceramics